Pendampingan Tata Kelola Keuangan pada Bumdes Desa Tlogosari Kec.Tirtoyudo - Ana Ana Khoirul Aisa; Yuda Ramadhani Yuda Ramadhani; Adita Nafisa Adita Nafisa (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
Village-Owned Enterprises (BUMDESA/BUMDes) are part of village institutional resources with economic scope. The main problem with BUMDes is the lack of management that occurred after the institution was officially formed. Moreover, the obstacles that are often indicated are problems regarding financial management procedures, in addition to other factors such as the limited capacity of BUMDes managers and weak supervisory functions. BUMDes managers have limited knowledge, understanding and ability to manage, administer and report business finances. This condition is an obstacle to business continuity and sustainable progress of BUMDes as a productive economic enterprise in the village which is expected to be able to support community welfare. So that community service activities are carried out through a pattern of providing assistance to BUMDes managers in Tlogosari Village, Tirtoyudo District who are experiencing problems, especially with financial reporting. This mentoring activity is carried out through three stages, namely observation, mentoring and evaluation. From the aspect of financial governance, it was found that the effectiveness of financial administration and the preparation of financial reports with accountability and transparency were weak. Keywords: BUMDes, Financial Governance.